Community-based interventions to improve prostate cancer screening and implications for black men: a scoping review - Adaji, Sunday; Adegoke, Adetoro A. (International Journal Of Community Medicine And Public Health, 2025)
The role of early detection of prostate cancer through prostate specific antigen (PSA) testing with or without digital rectal examination (DRE) to improve prostate cancer outcomes remains contentious, with ongoing debates about benefits and risks. Despite limitations, PSA testing with or without DRE remains the mainstay of early prostate cancer detection. Still, research findings have demonstrated underutilisation among black men who are most at risk. In this scoping literature review, three databases (PubMed NLM, CINAHL, and PsycINFO) were searched to identify and characterise community-based interventions to promote early detection of prostate cancer. Review studies, systematic or not, were excluded as well as studies that were not published in English, nor focused mainly on prostate cancer. Fifteen studies met the search criteria and were included in the review, with only one published in the UK, one in Iran, and 13 in the USA. The authors utilised community engagement strategies with faith-based groups, especially churches, making key contributions within American society. Decision aid tools to help men overcome their decisional conflicts and navigate to the point of screening were an important feature of many of the studies. Our findings suggest that well-designed and carefully tailored community-based interventions could contribute to creating awareness and informed decisions for PSA testing with or without DRE. In the UK society, such interventions are still required and should be prioritised without delay to help improve early prostate cancer detection among black men.